Protein targeting, transport & translocation (Academic Press, 2002)
This book presents an in-depth overview on the topic of protein synthesis, covering all areas of protein science, including protein targeting, secretion, folding, assembly, structure, localization, quality control, degradation, and antigen presentation. Chapters also include sections on the history of the field as well as summary panels for quick reference. Numerous color illustrations complement the presentation of material. This book is an essential reference for anyone in biochemistry and protein science, as well as an excellent textbook for advanced students in these and related fields.